2020
DOI: 10.3390/biomedicines8040095
|View full text |Cite
|
Sign up to set email alerts
|

Does Medication-Related Osteonecrosis of the Jaw Influence the Quality of Life of Cancer Patients?

Abstract: The aim of this study is to observe the influence of Medication-Related Osteonecrosis of the Jaw (MRONJ) on the physical and mental conditions of cancer patients using a Quality of Life (QoL) questionnaire during regular dental practice measures. Twenty cancer patients (8 males and 12 females) with established MRONJ were enrolled in the “MoMax” (Oral Medicine and Maxillofacial) project of the Department of Oral Sciences and Maxillofacial Surgery at “Sapienza” University of Rome, and were included in the study.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 33 publications
1
23
1
Order By: Relevance
“…Post-surgical follow-up must be appropriate to ensure complete healing. Drug holidays should be considered if systemic conditions permit reducing the risk of developing MRONJ and clinical symptoms [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Post-surgical follow-up must be appropriate to ensure complete healing. Drug holidays should be considered if systemic conditions permit reducing the risk of developing MRONJ and clinical symptoms [ 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…As in many cases, it can be hypothesized that all these effects may have a synergistic action and, to different degrees, they induce the pain-relieving effect so widely demonstrated in many studies in the literature [32]. So far, the PBM has been largely adopted in the management of the pain associated with the MRONJ and several studies emphasized this positive effect that improves the QoL of these patients [7,12,26]. Tenore et al [33], in a clinical trial performed in our Department at Sapienza University of Rome, observed a reduction of at least 4 points of the Numeric Rating Scale (NRS) pain score, in 88% of the 25 patients included in their study.…”
Section: Antalgic Applicationmentioning
confidence: 99%
“…In addition, many co-factors, such as comorbidities (e.g., diabetes), smoking, dental interventions, and concurrent medications (e.g., corticosteroids), have been reported to play a role in its pathogenesis [5]. Bone progressive exposure and pain are the most severe complications of MRONJ, and their onset was demonstrated to greatly reduce the Quality of Life (QoL) of patients [2,6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Bisphosphonate-Related Osteonecrosis of the Jaw (BRONJ) is a pathology widely discussed in the medical field. It is characterized the presence of non-scarring and necrotic exposed bone in the jaws or fistula for a minimum period of eight weeks in patients with a previous or current history of use of antiresorptive drugs, and who have not been submitted to head and neck radiotherapy (RUGGIERO et al, 2014;TENORE et al, 2020). Some local risk factors are described for the occurrence of BRONJ, such as periodontal disease, caries, periapical lesions, trauma caused by ill-fitting dentures and poor oral hygiene.…”
Section: Introductionmentioning
confidence: 99%